Corruption and democracy in post-2011 Tunisia: a confirmatory empirical analysis. (24th February 2022) - Belgacem, Ines; Lamari, Moktar; Trabelsi, Samir
This study examines the relationship between democracy and corruption in post-2011 Tunisia. The aim was to empirically identify the principles corruption factors that influence corruption and democracy and to test the effectiveness of corruption factors in democratic transition. The paper used survey data coming from Word Values Survey (2016) with a sample of 1, 205 persons from different Tunisian regions. After examining perceptions of corruption through confirmatory factor analysis, instrumental variable method was performed to check the reliability of the estimation of the regression coefficient causally linking democracy to corruption. The analysis shows that emerging democracy in Tunisia reduces corruption in a statistically significant way. Decision-makers will find in our paper's results new ideas helping government, parties and NGO to sensitise population about the democracy concept and how to reduce corruption by helping citizens to avoid corrupted transactions and informal collusions.